ExplanationFinding \(f (t + 54)\):

\(f(x) = 5x + 1\)

\(f(t + 54) = 5(t + 54) + 1\)

\(f(t + 54) = 5t + 270 + 1\)

\(f (t + 54) = 5t + 271\)

Now finding \(f (t + 50)\):

\(f(x) = 5x + 1\)

\(f (t + 50) = 5(t + 50) + 1\)

\(f (t + 50) = 5t + 250 + 1\)

\(f (t + 50) = 5t + 251\)

Now finding \(f (t + 54) - f (t + 50)\):

\(f (t + 54) - f (t + 50)\)

\(=(5t + 271) - (5t + 251)\)

\(=(5t + 271) - 5t - 251\)

\(271 - 251 =20\)

The two quantities are equal.

Hence option C is correct.
_________________

Sandy

If you found this post useful, please let me know by pressing the Kudos Button

Try our free Online GRE Test